The role of the LysR-type transcription factor PacR in regulating nitrogen metabolism in Anabaena sp. PCC7120 - Werner, Elisa; Huokko, Tuomas; Santana-Sánchez, Anita; Picossi, Silvia; Nikkanen, Lauri; Herrero, Antonia; Allahverdiyeva, Yagut (WILEY, 2025)
In the filamentous cyanobacterium Anabaena sp. PCC 7120, heterocyst formation is triggered by changes in the C/N-ratio and relies on transcriptional reprogramming. The transcription factor PacR is considered a global regulator of carbon assimilation under photoautotrophic conditions, influencing the carbon concentrating mechanism and photosynthesis. It plays a role in balancing reducing power generation while protecting the photosynthetic apparatus from oxidative damage. However, PacR also binds to promoters of genes associated with heterocyst formation, although the underlying mechanisms remain unclear. To explore this, we studied the response of a PacR-deletion mutant to a nitrogen source shift from ammonium to nitrate. The absence of PacR led to heterocyst formation in nitrate-containing media, as well as reduced growth and chlorophyll content. We observed impaired nitrate uptake and disrupted ammonium assimilation via the GS/GOGAT-cycle. This phenotype may stem from PacR-mediated regulation of key genes of nitrogen and carbon metabolism as well as photosynthesis. An impact on photosynthesis is also apparent in the mutant, including a slight decrease in the size of the photo-reducible Fed-pool, suggesting that a shortage of reducing equivalents may contribute to nitrogen metabolism impairment.